Characterization of heavy metal-associated bacteria from petroleum-contaminated soil and their resistogram and antibiogram analysis - Basit, Abdul; Andleeb, Saiqa; Liaqat, Iram; Ashraf, Nasra; Ali, Shaukat; Naseer, Anum; Nazir, Aisha; Kiyani, Fahad (Folia microbiologica, 2024)
The aim of the current study was to screen and identify heavy metal (chromium, cadmium, and lead) associated bacteria from petroleum-contaminated soil of district Muzaffarabad, Azad Jammu and Kashmir, Pakistan to develop ecofriendly technology for contaminated soil remediation. The petroleum-contaminated soil was collected from 99 different localities of district Muzaffarabad and the detection of heavy metals via an atomic absorption spectrometer. The isolation and identification of heavy metals-associated bacteria were done via traditional and molecular methods. Resistogram and antibiogram analysis were also performed using agar well diffusion and agar disc diffusion methods. The isolated bacteria were classified into species, i.e., B. paramycoides, B. albus, B. thuringiensis, B. velezensis, B. anthracis, B. pacificus Burkholderia arboris, Burkholderia reimsis, Burkholderia aenigmatica, and Streptococcus agalactiae. All heavy metals-associated bacteria showed resistance against both high and low concentrations of chromium while sensitive towards high and low concentrations of lead in the range of 3.0 ± 0.0 mm to 13.0 ± 0.0 mm and maximum inhibition was recorded when cadmium was used. Results revealed that some bacteria showed sensitivity towards Sulphonamides, Norfloxacin, Erythromycin, and Tobramycin. It was concluded that chromium-resistant bacteria could be used as a favorable source for chromium remediation from contaminated areas and could be used as a potential microbial filter.
Keywords: Microbial Sensitivity Tests; Pakistan; Metals, Heavy; Resistogram analysis; Ribotyping; olovo; Petroleum; Heavy metals; Soil Pollutants; látky znečišťující půdu; mikrobiální testy citlivosti; půda; Lead; antibakteriální látky; Bacillus spp; Chromium; Cadmium; těžké kovy; Anti-Bacterial Agents; Petroleum contaminated soil; chrom; půdní mikrobiologie; ropa; Pákistán; kadmium; Bacteria; Soil; Antibiogram analysis; Soil Microbiology